Proteomic analysis of immunogenic proteins from salivary glands of Aedes aegypti - Rike Oktarianti; Kartika Senjarini; Toshiya Hayano; Fatchiyah Fatchiyah; Aulanni'am (Elsevier, 2015)
Summary: Humans develop anti-salivary proteins after arthropod bites or exposure to insect salivary proteins. This reaction indicates that vector bites have a positive effect on the host immune response, which can be used as epidemiological markers of exposure to the vector. Our previous study identified two immunogenic proteins with molecular weights of 31 kDa and 56 kDa from salivary gland extract (SGE) of Aedes aegypti that cross-reacted with serum samples from Dengue Hemorrhagic Fever (DHF) patients and healthy people in an endemic area (Indonesia). Serum samples from individuals living in non-endemic area (sub-tropical country) and infants did not show the immunogenic reactions. The objective of this research was to identify two immunogenic proteins, i.e., 31 and 56 kDa by using proteomic analysis. In this study, proteomic analysis resulted in identification of 13 proteins and 7 proteins from the 31 kDa- and 56 kDa-immunogenic protein bands, respectively. Among those proteins, the D7 protein (Arthropode Odorant-Binding Protein, AOBP) was the most abundant in 31-kDa band, and apyrase was the major protein of the 56-kDa band. Keywords: Proteomic analysis, Immunogenic proteins, Salivary gland, Aedes aegypti